Antifungal activity of Parastrephia quadrangularis (Meyen) Cabrera extracts against Fusarium verticillioides - Di Ciaccio, Lucía Soledad (2018)
Fungi are cosmopolitan organisms that grow in and adapt to a vast number of substrates and environments, and that can cause diseases in humans and animals, as well as in crops. The vast area and diverse geographical characteristics of Argentina, with the consequent climatic diversity make the country an important source of biological resources suitable for the search of new compounds. The aim of the present study was to describe the antifungal activity of extracts of Parastrephia quadrangularis, a species from northern Argentina, against Fusarium verticillioides M7075. Bio‐guided fractionation and MS/MS studies were conducted to elucidate the chemical structure of active compounds. The extracts exhibited a minimum inhibitory concentration among 118·74 and 250 μg ml−1 and the differences between the treatments and the inoculum control was 12·5–16·5 mm, respectively, in colony growth. Moreover, hyphae treated with the extracts stained blue with Evans blue, showed alterations in permeability of plasma membranes. HLPC‐MS analysis of active fractions revealed the presence of p‐coumaroyloxitremetone, and a derivate structure for another compound is proposed.